PEMBINAAN AGAMA ISLAM DI SEKOLAH LUAR BIASA (SLB) - Syahruddin Syahruddin; Alimuddin Alimuddin (Institut Agama Islam Negeri (IAIN) Palopo, 2022)
Islamic religious education is a right for every Muslim, including for children with special needs. Religious guidance to them is not as easy as that of normal children. They have their own pattern in conveying the material so that what is conveyed can be understood and practiced in everyday life. Educators must be able to carry out coaching by using learning patterns that suit their needs. This research is a type of field research using qualitative descriptive research. The which aims of this reaeach to determine the development of Islam in SLB Negeri 1 Palopo, as well as the factors supporting and inhibiting the development of Islam in SLB Negeri 1 Palopo. Data was collected by means of observation, interviews, and documentation. Data were analyzed by doing data reduction, then presented for analysis to draw conclusions. The results showed that the development of Islamic religion in SLB Negeri 1 Palopo was different according to the type of need. For the deaf, coaching is done using visual media. For people with visual impairments, coaching is done by using books that use embossed writing. For people with mental retardation, coaching is focused on forming good morals and character through habituation of smiles, greetings, and greetings. Meanwhile, for people with disabilities, educators and guardians of students work together intensively to provide guidance. The materials presented are faith, worship, morality, and character.